Desenvolvimento e otimização de péletes de liberação bifásica mediante delineamento experimental - Martins, Sarah Moherdaui (2015)
In recent years, the interest of the pharmaceutical industry for new drugs delivery system has been growing, especially aiming the optimization of therapy and reduction of side effects caused by conventional treatments. The multiparticulate systems, besides their techonological and biopharmaceutical advantages when compared to the monolithic systems, allow obtaining different ways of drug delivery, such as the biphasic system, capable of delivering the drug in separate fractions into the bloodstream, and ideal for the treatment of circadian diseases. Thus, this study aimed to obtain a multi particulate system biphasic release, lasting 24 hours, using a combination of polymeric materials hydroxypropyl methylcellulose and ethyl cellulose, as well as a full factorial design 2² to optimize the development stage. Furthermore, it was developed and validated analytical method by UV spectroscopy able to quantify the model drug used, propranolol hydrochloride (PROP) test and the content of dissolution of the dosage form. Using the sugar spheres coating technology, it was possible to obtain the proposed system with a reduced number of experiments. Pellets produced and used in the biphasic formulations showed mechanical characteristics within the expected quality parameters, showing that the technique is robust and can be applied on an industrial scale. The analytical method for the quantification of the proposed drug was linear, precise, accurate, robust against variations in wavelength of mark and sonication solvent in a concentration range of 0.80 - 96 mg L-1 and stable the experimental conditions analyzed, showing a method capable of generating highly reliable results and therefore able to be used in the laboratory routine quality control.